The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acsami.5b02194
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Hierarchical Alumina–Graphene Oxide–Poly(vinyl alcohol) Artificial Nacre with Optimized Strength and Toughness

Abstract: Due to hierarchical organization of micro- and nanostructures, natural nacre exhibits extraordinary strength and toughness, and thus provides a superior model for the design and fabrication of high-performance artificial composite materials. Although great progress has been made in constructing layered composites by alternately stacking hard inorganic platelets and soft polymers, the real issue is that the excellent strength of these composites was obtained at the sacrifice of toughness. In this work, inspired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
75
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 46 publications
0
75
1
2
Order By: Relevance
“…In the resulting composites, smooth structural integration is expected due to GO’s 2D structure and the presence of oxygen-containing functional groups located on the basal planes. In contrast to previous reports242527, such a ternary system features an “inverse” composition with a small amount of soft component embedded into a comparatively harder matrix. The interaction between the different building blocks should lead to a unique combination of high tensile strength, good toughness, as well as excellent stiffness in a synergistic fashion.…”
contrasting
confidence: 66%
See 2 more Smart Citations
“…In the resulting composites, smooth structural integration is expected due to GO’s 2D structure and the presence of oxygen-containing functional groups located on the basal planes. In contrast to previous reports242527, such a ternary system features an “inverse” composition with a small amount of soft component embedded into a comparatively harder matrix. The interaction between the different building blocks should lead to a unique combination of high tensile strength, good toughness, as well as excellent stiffness in a synergistic fashion.…”
contrasting
confidence: 66%
“…The interaction between the 1D and 2D building blocks can lead to sliding effects, crack deflection and crack bridging, thereby enhancing the strength and toughness of such composite materials in a synergistic manner2122. Recently, several studies have addressed the design and mechanical characterization of ternary artificial nacre232425262728. For instance, Wang et al 24.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the strength and toughness among the ternary artifi cial nacres with different AA contents, it becomes clear that a higher content of AA led to higher failure strength and higher toughness (Figure 3 b). To further verify the advantages of our novel ternary artifi cial nacres, the tensile strength and toughness of natural nacre and all GO/rGO-based nacre-inspired fi lms are summarized in Figure 3 c. [ 24,31,32,34,[38][39][40][41][42][43][44][45][46] It can be seen that the tensile strength and toughness of the ternary GO-AA-SCMC-III artifi cial nacre were 2.3-times and 4.3-times higher than that of natural nacre, [ 34 ] which only showed a tensile strength of 80-130 MPa and toughness of 1.8 MJ m −3 . On the contrary, in the binary GO/rGO-based artifi cial nacres, only one of the mechanical properties (strength or toughness) can be improved at the cost of the other.…”
Section: Doi: 101002/adma201505511mentioning
confidence: 99%
“…Unfortunately, the properties of toughness and strength are mutually exclusive. Recently, researchers have demonstrated that ternary artifi cial nacres reinforced by a third reinforcement agent, such as nanofi brillar cellulose, [ 29 ] carbon nanotubes, [ 30 ] Al 2 O 3 , [ 31 ] or MoS 2 , [ 32 ] show a simultaneous increase in both strength and toughness, which makes them superior to natural nacre [ 2 ] and artifi cial binary nacre.[ 8 ] However, the random addition of a third component into the binary composites during the preparing process does not guarantee a perfect match of the third reinforcement agent with the original brick and mortar structure, thus this may lead to a limited improvement in strength and toughness.Herein, a new type of ternary artifi cial nacre (graphene oxide (GO)/ultrathin amorphous alumina (AA)/sodium carboxymethyl cellulose (SCMC)) has successfully been synthesized by a simple vacuum-assisted fi ltration method. In order to guarantee the uniform layered nacre-like structure of this new product for the fi rst time, the ultrathin amorphous alumina (AA) was grown in situ on the surface of GO with a thickness varying from around 1 nm to 10 nm before mixing this together with the polymer SCMC.…”
mentioning
confidence: 99%